STUDY OF ORGANIC POLLUTION OF SURFACE WATERS OF THE RIVER IN THE ZONE OF ANTHROPOGENIC IMPACT OF WATER DISCHARGE - Biedunkova Ольга; Kuznietsov Павло (Biota. Human. Technology, 2025)
Objective. The purpose of the study was to analyze the impact of RNPP water discharges on the water quality of the Styr River by the organic pollution indices (OPI). The objectives of the study included monitoring changes in organic pollution concentrations by the following indicators: biochemical oxygen demand (BOD5), chemical oxygen demand (COD), nitrate (NO3–), ammonium nitrogen (N–NH3), nitrite (NO2–), orthophosphate (PO43–) and dissolved oxygen (DO) concentrations in the water of the Styr River in the zone of influence of the Rivne Nuclear Power Plant (RNPP) water discharge and calculation of the OPI by different methods. The object of the study is the surface waters of the Styr River, in particular, their organic pollution by the values of the OPI. The subject of the study is the variations of the OPI calculated by different methods and their dynamics under the influence of anthropogenic factor of influence of water discharge from the RNPP. Methodology. The study covered the period of 2020–2022 and was based on the analysis of chemical indicators: BOD5, COD, NO3–, N–NH₃, NO2–, PO43–, and DO. Several calculation methods and statistical analysis of the data were used to determine the dynamics of the OPI. The assessment of the ecological state of the Styr River was carried out in accordance with the standards of maximum allowable concentrations (MAC) for fishery and domestic water bodies. Scientific novelty. The study provides a comprehensive analysis of the dynamics of organic pollution of the Styr River in the RNPP impact zone, taking into account different methods of calculating the OPI. The applied approaches allow us to adapt the research methods for other water bodies, which is important for improving environmental monitoring. Conclusions. The results of the study show that the water of the Styr River mostly corresponds to the ‘clean’ state according to the OPI, but there were some periods of exceeding the thresholds. In the warm season, organic pollution increases due to an increase in COD and BOD₅, while in the winter season, the accumulation of NO₃– dominates, and the maximum concentrations of N–NH₃ often exceeded the MAC for fisheries, indicating impact of organic pollution.